2017
DOI: 10.1128/mbio.00590-17
|View full text |Cite
|
Sign up to set email alerts
|

Kisameet Glacial Clay: an Unexpected Source of Bacterial Diversity

Abstract: Widespread antibiotic resistance among bacterial pathogens is providing the impetus to explore novel sources of antimicrobial agents. Recently, the potent antibacterial activity of certain clay minerals has stimulated scientific interest in these materials. One such example is Kisameet glacial clay (KC), an antibacterial clay from a deposit on the central coast of British Columbia, Canada. However, our understanding of the active principles of these complex natural substances is incomplete. Like soils, clays m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 68 publications
(89 reference statements)
1
27
0
Order By: Relevance
“…Exchangeable metal ions have been reported to be responsible for the activity of some antibacterial clays (35)(36)(37). We and others have previously found that the mineralogical composition and chemical properties of KC differ from those of other known natural antibacterial clay minerals (43,46,52). Next, we investigated if the exchangeable/soluble fraction of the clay might be involved in KC activity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Exchangeable metal ions have been reported to be responsible for the activity of some antibacterial clays (35)(36)(37). We and others have previously found that the mineralogical composition and chemical properties of KC differ from those of other known natural antibacterial clay minerals (43,46,52). Next, we investigated if the exchangeable/soluble fraction of the clay might be involved in KC activity.…”
Section: Resultsmentioning
confidence: 96%
“…Our previous studies showed that aqueous suspensions of KC exhibit potent antibacterial activity against the clinically important ESKAPE pathogens in vitro (45). We also characterized the geochemical and microbiological features across the KC deposit to obtain insight into what might make the clay active (46). This revealed a surprising level of bacterial species richness and prevalence of iron bacteria such as Gallionella species near the surface of the deposit, provided molecular evidence for taxa that include medically or economically important bacteria such as Actinomycetes, and in general highlighted the complexity and diversity of the KC deposit.…”
mentioning
confidence: 99%
“…Unlike Streptomyces discovered from the golden age of antibiotic discovery in the mid-20th century, traditional medicine soils are specific in their locations such as the Boho clay, or in their type such as glacial clay from Canada [52,53]. Clay, which has long been thought to be therapeutic in itself, is also home to a diverse array of Streptomyces [22,[52][53][54]. Traditional glacial clay from Kisameet Bay in Canada has been used for millennia by the Heiltsuk people against skin infections [52].…”
Section: Streptomyces From Traditional Soil-based Medicinementioning
confidence: 99%
“…It is quite typical to find multiple species of Streptomyces in traditional medical preparations such as soil or moonmilk [50,54,64]. Now, it has been discovered that competition and collaboration between Streptomyces and other species can also awaken silent antibiotic-synthesis clusters [65].…”
Section: Co-cultivationmentioning
confidence: 99%
“…Analyses of different clay layers of coastal subseafloor sediments from Okhotsk sea identified a variety of bacteria and archaea, such as green non-sulfur bacteria and deep sea archaeal group (Inagaki et al, 2003). Different groups of bacteria were found in the Opalinus clay rock from Mont Terri, Switzerland and Kisameet Glacial clay from British Columbia, Canada, whose functions range from CO 2 fixation to sulfate reduction (Bagnoud et al, 2016a,b;Svensson et al, 2017). Thus, a phylogenetically and physiologically diverse groups of bacteria and archaea are associated with subsurface clay layers.…”
Section: Introductionmentioning
confidence: 99%